2022
DOI: 10.3390/molecules27154878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Denaturants on the Properties of a Hot-Pressed Peanut Meal-Based Adhesive

Abstract: Plant protein-based adhesives could fundamentally solve the problem of formaldehyde-based adhesive releasing formaldehyde, but enhancing bonding strength and water resistance is a necessary measure to realize practical applications. In this study, the effects of different denaturants on the properties of a hot-pressed peanut meal (HPM)-based adhesive before and after crosslinking were studied. Papain, sodium dodecyl sulfate (SDS), urea and crosslinker-polyamide epichlorohydrin (PAE) were used to prepare HPM-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The peaks observed near 1662, 1540, and 1240 cm −1 were attributed to the -C=O stretching vibration (amido band I), the N-H bond bending vibration (amido band II), and the C-N stretching and N-H bending vibration (amido band III) [50], respectively. At 1720 cm −1 , the absorption peak was attributed to the ester bond [51] inside sunflower seed meal protein, and the absorption intensity of oil sunflower was greater than that of edible sunflower. The fitting secondary structure of sunflower seed meal protein is shown in Figure 5C.…”
Section: Ftir Analysis Of Sunflower Seed Protein Powdermentioning
confidence: 99%
“…The peaks observed near 1662, 1540, and 1240 cm −1 were attributed to the -C=O stretching vibration (amido band I), the N-H bond bending vibration (amido band II), and the C-N stretching and N-H bending vibration (amido band III) [50], respectively. At 1720 cm −1 , the absorption peak was attributed to the ester bond [51] inside sunflower seed meal protein, and the absorption intensity of oil sunflower was greater than that of edible sunflower. The fitting secondary structure of sunflower seed meal protein is shown in Figure 5C.…”
Section: Ftir Analysis Of Sunflower Seed Protein Powdermentioning
confidence: 99%
“…The SP/BGP-PA-T adhesive had the highest shear strength, which demonstrated that the protein hybridization and molecular reorganization strategies signicantly enhanced the mechanical strength of the adhesive. 50,[64][65][66][67][68][69] The wet shear strengths of bio-based adhesives such as lignin, 70,71 starch, sucrose, tannic acid, blood meal, soybean meal and SP/BGP-PA-T were compared; SP/BGP-PA-T also exhibited excellent mechanical strength. [72][73][74][75] SP/BGP-PA-T showed superior wet shear strength compared to peanut meal-based, cotton meal-based, maize protein, wheat gluten, sesame protein and casein adhesives.…”
Section: Performance Of the Spi Bgp And Sp/bgp-based Adhesivesmentioning
confidence: 99%
“…The findings revealed that the replacement of fish meal with peanut meal did not yield any significant effects on growth performance, feed utilization, somatic indices, or whole-body composition (p > 0.05). Li et al [107] used peanut meal as a substitute for the original cottonseed protein or soybean protein in the diets of Channel Catfish. Following a 9-week investigation, the findings demonstrated that peanut meal can effectively replace up to 25 wt% of the original cottonseed meal or soybean meal without any detrimental impact on fish growth, feed efficiency, and the body composition of fish.…”
Section: Solid-state Fermented By Bacillus Licheniformismentioning
confidence: 99%